Critical Discourse Analysis: The Knowledge Power Presented by Scholar in Creating Research Article - Tisa Arum Wardani; Slamet Setiawan; Pratiwi Retnaningdyah (Linguistic, English Education and Art (LEEA) Journal, 2020)
This study was aimed to analyse the background study on research article and put the argumentation based on the theory about critical discourse analysis related to social cognition theory. Furthermore, the researcher wanted to compare 2 article in critical discourse analysis approach. This method on this study is descriptive qualitative which is presented in the positivist views. Then the result was generalized in the relation on finding and discussion with the theory. In summary, the result showed the different ways in giving the power of the argumentation and explanation between RA1 and RA2. In conclusion, the power of argument used will lead the reader to ignore or accept on how it is become valid statement or not. Keywords: Social Cognition, Critical Discourse Analysis, Background Study